Infant feeding, growth monitoring and the double burden of malnutrition among children aged 6 months and their mothers in KwaZulu‐Natal, South Africa. Issue 1 (29th November 2021) - Kaldenbach, Siri; Engebretsen, Ingunn M. S.; Haskins, Lyn; Conolly, Catherine; Horwood, Christiane
Abstract: South Africa has a documented high prevalence of stunting and increasing obesity in children as well as obesity in adults. The double burden of malnutrition, which can be on an individual‐, household‐ or population level, has implications for both health and the economic development of a community and country. This paper describes a large‐scale survey ( N = 774) of infant feeding, growth monitoring and anthropometry among mother and child pairs aged 6 months of age in KwaZulu‐Natal (KZN), South Africa, conducted between January and August 2017. Among children, a large increase in the prevalence of stunting and obesity was seen between birth and 6 months of age increasing from 9.3% to 21.7% and 4.0% to 21.0%, respectively. 32.1% of the mothers were overweight [body mass index (BMI): 25.0–29.9] and 28.4% had obesity grade 1 (BMI: 30–<40). Although most mothers (93%; 563/605) initiated breastfeeding, the introduction of other foods started early with 17.6% (56/319) of the mothers having started giving other fluids or food to their child within the first month. At 6 months 70.6% (427/605) children were still breastfed and 23.5% were exclusively breastfed. In addition, we found that length measurements were done less frequently than weight measurements between birth and 6 months, on average 2.2 (SD: 1.3) versus 5.8 (SD: 1.5) times. Moreover, there is a need for improvement of health worker training and understanding regarding anthropometric measurements when assessing malnutrition in children in the clinics. Early detection and improved infant feeding practices are key in preventing both stunting and obesity in children. Key messages: The double burden of malnutrition is severe in KwaZulu‐Natal with high rates of maternal obesity and increasing prevalence of stunting and obesity among infants in the first 6 months of life. Breastfeeding and complementary feeding practices are suboptimal and additional support for breastfeeding is required in the post‐natal period and in the workplace to address breastfeeding challenges. Growth monitoring is inadequate in health facilities leading to many lost opportunities for early identification of malnutrition. Hence, anthropometric practices and interpretation of findings need to be strengthened. Abstract : The double burden of malnutrition is prevalent in South Africa with high rates of obesity among mothers, and increasing stunting and obesity among children during the first 6 months of life. This is potentially driven by poor breastfeeding and complementary feeding practices. As a result, improved training and facilitation for safer nutritional practices are warranted.